Fenomena Fear of Floating Nilai Tukar di Indonesia Periode 1998-2007: Identifikasi, Alasan Ekonomi, dan Implikasinya terhadap Kebijakan Moneter - Budiasih, Budiasih (Jurnal Ekonomi dan Pembangunan Indonesia, 2011)
The stable fluctuation of Rp against the US$ during the free floating exchange rate regime in 2002-2007 raises the existence of fear of floating exchange rate phenomenon in Indonesia. The GARCH method is use to verify this phenomenon. Moreover, Time Varying Parameter and Error Correction Mechanism method shows the economic reason behind the Monetary Authority's response in stabilizing rupiah. Depreciation and increasing volatility of Rupiah raises inflation and bank Non-Performing Loans, while appreciation and increasing volatility of Rupiah, reduce the net export. Furthermore, Vector Autoregressive confirms the Monetary Authority respond to exchange rate shock through the interest rate policy for four months and through the foreign reserves policy for two months.